A cross-sectional study evaluating the prevalence and predictors of malnutrition among children and adolescents visiting an urban academic hospital in Nepal - Ram Chapagain; Bishnu Giri; Tribhuwan Bhattarai; Juna Dhungana; Michelle Walters; Erika Damasco; Jessica Blanco; Kyriaki D Ladas; Andreas Antoniades; Elena Ladas (Cambridge University Press, 2023)
Abstract Objective: To examine the prevalence of malnutrition among children and adolescents visiting Kanti Children's Hospital (KCH) and identify predictors associated with malnutrition. Results will guide the development of a newly established nutrition programme at KCH. Design: This cross-sectional pilot study recruited children and adolescents over a 1-month period. Nutritional anthropometrics (height, weight and mid-upper arm circumference (MUAC)) and socio-demographic questionnaires were administered. Clinical data were abstracted from the medical chart. Setting: KCH in Kathmandu, Nepal. Participants: 370 children and adolescents. Results: Most participants were male (65·1 %); mean age was 3·9 years (±3·4 years). The prevalence of stunting was 25·9 %, wasting was 17·3 % and 24·0 % when classified by BMI-for-age Z-score or MUAC, respectively. Two percent of participants were overweight. Notably, 32·1 % of children ≥5 years were classified with wasting based on MUAC-for-age Z-score, which is higher than that observed in children <5 (20·2 %). Food insecurity was reported among 58·2 % of children with stunting and 34·0 % with wasting. Chronic medical conditions predicted stunting and wasting. The lowest level of wealth predicted stunting, while ethnicity predicted wasting. Ethnicity and education level predicted food insecurity. Conclusions: We found that the prevalence of stunting and wasting at KCH are higher than previously published studies in Nepal. Malnutrition persists beyond 5 years, and we identified several predictors of malnutrition. Increased provision of and access to clinical nutrition programmes is an essential need for KCH. Twinning programs that provide local clinicians with increased opportunities for education and mentorship of local staff remains a pressing need in Nepal.